Volatile fatty acids recovery from thermophilic acidogenic fermentation using hydrophobic deep eutectic solvents - Can Liu; Xueyao Zhang; Qi Qiao; Zhiwu Wang; Qing Shao; Jian Shi (Journal of Biological Engineering)
Abstract Background Volatile fatty acids (VFA) derived from acidogenic fermentation can be recovered as precursors for synthesizing value-added chemicals to replace those from fossil fuels. However, separating VFAs from the fermentation broth with complex constituents and a high-water content is an energy-intensive process. Results This study developed an innovative membrane extraction technology, utilizing hydrophobic deep eutectic solvents (HDESs) as the acceptor phase along with an omniphobic membrane contactor for efficient extraction of anhydrous VFAs. All tested HDESs, three terpene-based type V HDESs and two tetraalkylammonium halide-based type III HDESs, were found to effectively extract VFAs at pH 3, with extraction recovery percentages (ERPs) up to 80% and 92% for 4 C- and 5 C- VFAs, respectively. However, the ERP of type V HDESs decreased significantly when the aqueous phase was adjusted to pH 6. Molecular simulations suggest that the VFA-HDES interactions vary with VFA dissociation, where the ion-dipole interactions between VFA conjugate bases and hydrogen bond donors at near-neutral pH conditions may destabilize the type V HDES structure and lead to reduced extraction efficiency. The temperature increases from 25 °C to 55 °C did not significantly impact VFA distribution, but a higher temperature could enhance cross-membrane mass transfer. Conclusions This study demonstrated a novel continuous VFA extraction technology based on HDESs and elucidates the impact of temperature, pH, impurities in real fermentate and the applicability of an integrated membrane system through combined experimental and computational approaches.